Ablation treatment of CFRP via nanosecond pulsed Ytterbium-doped fiber laser: Effects of process parameters on surface morphology and shear strength of adhesive bonded joints - Chiara Mandolfino; Fabrizio Moroni; Marco Pizzorni (Journal of Advanced Joining Processes)
Adhesive bonding is the joining technique that provides the maximum exploitation of Carbon Fiber Reinforced Polymers (CFRPs) for structural applications. However, it is necessary to attain a high-strength adhesive bond, achieved by removing surface contaminants, such as mold release agents, and simultaneously generating a surface structure suitable to increase the actual contact surface area. The purpose of the research work presented in this paper is to evaluate the effect of process parameters of a nanosecond pulsed laser pre-bonding surface treatment on the ablation of thermoset matrix CFRP substrates. In particular, the link between the volume of ablated material and the tensile shear strength (TSS) of adhesive bonded joints was evaluated by lap-shear tests, profilometer surveys, and Scanning Electron Microscope (SEM) analysis. ANOVA and regression models were used to highlight the influence of laser parameters, with power emerging as the most significant factor, and energy density proving pivotal for joint strength. Line spacing was also significant, while scanning direction had negligible impact. The key outcomes of the study demonstrated that controlled laser ablation plays a critical role in determining joint performance. A negative correlation was found between TSS and the thickness of ablated material, indicating that excessive ablation weakens the bond. Optimal joint strength was achieved with moderate fiber exposure while maintaining matrix integrity, emphasizing the need for precise control over laser parameters. Fracture surface analyses revealed distinct failure mechanisms, ranging from cohesive failure within the adhesive layer to interfacial failure at the fiber-matrix boundary, depending on the ablation conditions. The findings provide clear guidelines for optimizing laser surface treatments to enhance the structural performance of CFRP adhesive joints in practical applications.